Diversification of the phaseoloid legumes: effects of climate change, range expansion and habit shift - Li, Honglei; Wang, Wei; Lin, Li; Zhu, Xiangyun; Zhu, Xinyu; Li, Jianhu; Chen, Zhiduan (Frontiers in Plant Science, 2013)
Understanding which factors have driven the evolutionary success of a group is a fundamental question in biology. Angiosperms are the most successful group in plants and have radiated and adapted to various habitats. Among angiosperms, legumes are a good example for such successful radiation and adaptation. We here investigated how the interplay of past climate changes, geographical expansion and habit shifts have promoted diversification of the phaseoloid legumes, one of the largest clades in the Leguminosae. Using a comprehensive genus-level phylogeny from three plastid markers, we estimate divergence times, infer habit shifts, test the phylogenetic and temporal diversification heterogeneity, and reconstruct ancestral biogeographical ranges. We found that the phaseoloid lineages underwent twice dramatic accumulation. During the Late Oligocene, at least six woody clades rapidly diverged, perhaps in response to the Late Oligocene warming and aridity, and a result of rapidly exploiting new ecological opportunities in Asia, Africa and Australia. The most speciose lineage is herbaceous and began to rapidly diversify since the Early Miocene, which was likely ascribed to arid climates, along with the expansion of seasonally dry tropical forests in Africa, Asia and America. The phaseoloid group provides an excellent case supporting the idea that the interplay of ecological opportunities and key innovations drive the evolutionary success.